Influence of argon pressure on the structural properties of polycrystalline sputtered Fe0.89Ga0.11 thin films - Ramírez,G.A.; Moya-Riffo,A.; Gómez,J.E.; Malamud,F.; Rodríguez,L.M.; Fregenal,D.; Bernardi,G.; Butera,A.; Milano,J. (AIP Publishing)
Fil: Ramírez, G. A. Comisión Nacional de Energía Atómica. Instituto de Nanociencia y Nanotecnología; Argentina